Synthesis and Characterisation of Thymol-Based Hydrophobic Deep Eutectic Solvents - Deborah Oluwatomilola Adeoye; Zaharaddeen Sani Gano; Omar Umar Ahmed; Suleiman Mohammed Shuwa; Abdulazeez Yusuf Atta; Baba Yakubu Jubril (Chemistry Proceedings)
The evolution of Hydrophobic Deep Eutectic Solvents (HDESs) has expanded the applications of the new generation of solvents, known as Deep Eutectic Solvents (DES), to include water-based operations. How stable they are in aqueous media qualifies them to be categorised as hydrophobic. This also determines whether they are appropriate materials for water-based industrial processes or not or whether they end up constituting a greater pollution load than those processes due to the leaching of their precursors into the aqueous media when used. This work sought to prepare HDESs from a monoterpene (thymol), and three long-chain organic acids (octanoic acid, decanoic acid, and dodecanoic acid). The physicochemical characteristics of the prepared HDESs were investigated. Thereafter, their moisture absorption capacity and stability in an aqueous environment were determined to ascertain whether they are hydrophobic as predicted.